Internalisasi Nilai Pendidikan Islam Berbasis Kearifan Lokal: Analisis Praktik Tradisi Ngejalang Kubokh dalam Pembentukan Sikap Sosial dan Religius Masyarakat - Nopia, Eni; Anwar, Chairul; Kesuma, Guntur Cahaya (Sekolah Tinggi Agam Islam Sumatera Medan, 2022)
This study aims to analyze the practice of the ngejalang kubokh tradition as the formation of social and religious attitudes of the people of Pekon Negeri Ratu Tenumbang, South Coastal District, West Coast District. This study used a descriptive qualitative research method. Primary data regarding the practice of ngejelang was obtained from research informants, namely traditional leaders, religious leaders, saibatin, village heads and parat pekon, as well as the implementing committee. Secondary data obtained from books, journals, and other relevant sources. The results showed that the internalized values ​​of the ngejalang kubokh tradition were religious values, educational values, social values and cultural values. The Ngejelang tradition is a form of local wisdom presented form a social order that is religious, harmonious, dynamic and socialist which is a form of the culture of people's lives. The execution of running the kubokh is carried out during one Shawwal. Talibun and pahakh as forms of local wisdom which become symbols in the implementation of bitch kubokh which have a sacred essence in them. The people of Pekon Negeri Ratu Tenumbang interpret the bitch tradition as one of the ways to increase a sense of kinship, maintain friendly ties so as to form social integration between communities.